Die invloed van inligtingstegnologie op werkverskaffing in die Suid-Afrikaanse finansiële sektor - Gideon S. Hom; Charles V.R. Wait (South African Journal of Business Management, 1992)
– The influence or information technology on the provision of employment in the South African financial sectorThe higher levels of productivity in the manufacturing sector, as a result of the automation and other significant changes in production functions, often lead to fears of higher levels of unemployment, as certain types of labour could become redundant. The application of information technology in the form of computers, data banks and telecommunication networks has, to a great extent, contributed to the automation of routine functions, as well as to the integration of various production functions. The danger exists that a great number of workers released from the manufacturing sector are not always trained and suitable for employment in the service sector. In addition, there may not be sufficient employment opportunities to accommodate these workers. The influence of information technology on employment should, however, be considered in terms of the net effect of the three distinguishing effects of information technology on an economy, namely the process, product and organization effects. In South Africa, employment and value added increased in the building society and banking fields during the period 1980-89. Those increases are attributed specifically to the product effect. Since the eighties, banks, building societies and insurance companies have all started to market new and more products that are directly linked to information technology.
Keywords: 650